Obstacles of Sustainable Agricultural Development from The Point Of View Of Agricultural Extension Workers In Sulaimani Governorate* - yasin, Lana; Sahab Ayid Al-Ajeili (University of Thi-Qar Journal of agricultural research, 2025)
The study aimed to identify the obstacles facing sustainable agricultural development from The Point Of View Of agricultural extension workers in Sulaymaniyah Governorate in general, as well as to identify these obstacles in each of the development dimensions (social, economic, and environmental), in addition to arranging the dimensions in descending order of importance. It also aimed to find the variance between the obstacles to sustainable development them and a group of independent variables. The research population comprised all agricultural extension personnel employed at the extension centres within Sulaymaniyah Governorate, totalling 93 workers in agricultural extension. Theseworkers were distributed throughout the various districts and sub-districts of the governorate;The research results revealed  that the obstacles facing the achievement of sustainable development are average and tends to rise in general in all its fields as well as in each field of the three dimensions of sustainable agricultural development. The results showed that the field of the economic dimension came in first rank  when arranging these fields according to their importance. These results also showed that the respondents did not show a difference in their opinions towards achieving sustainable agricultural development with the variables of age, academic achievement and participation in training courses, while they showed a varaince with the variables of information sources and the attitude towards sustainable agricultural development. The research concluded that there are serious and major obstacles hindering the achievement of sustainable agricultural development in Sulaymaniyah Governorate. The research recommended making efforts and activating the role of agricultural extension and other development organizations to address these obstacles.